Factor Risk Premia During The COVID-19 Pandemic: Evidence from Chinese Stock Markets - Qiao, Kenan (Eximia, 2022)
This study investigates the impact of new COVID-19 cases on the factor risk premia in Chinese stock markets. Fama-Macbeth’s two-pass procedure is applied to estimate the timevarying risk premia associated with Fama and French’s (2015) five factors. I assess the impact of new COVID-19 cases on factor risk premia by bivariate vector autoregressive models. Empirical results show that new COVID-19 cases negatively affect the market risk premium but significantly increase the size premium in Chinese stock markets. These findings shed light on the influence of COVID-19 on the factor structure and risk premia in equity markets.